2017
DOI: 10.1111/jhn.12491
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of change in dietitians’ perceived comprehensibility and difficulty of the Patient‐Generated Subjective Global Assessment (PGSGA) after a single training in the use of the instrument

Abstract: Evaluation of change in dietitians' perceived comprehensibility and difficulty of the PatientGenerated Subjective Global Assessment (PG-SGA) after a single training in the use of the instrument Sealy, M. J.; Ottery, F. D.; van der Schans, C. P.; Roodenburg, J. L. N.; Jager-Wittenaar, H. Abstract Background: The Patient-Generated Subjective Global Assessment (PG-SGA) is an instrument used to assess malnutrition and its risk factors. Some items of the PG-SGA may be perceived as hard to comprehend or as difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…The results of the current study supports the recommendation to train HCPs in the use of the PG-SGA prior to using it in daily practice [16]. A study in Dutch dietitians has demonstrated that already a full day training is very effective in improving both comprehensibility and difficulty of the PG-SGA [22].…”
Section: Discussionsupporting
confidence: 82%
“…The results of the current study supports the recommendation to train HCPs in the use of the PG-SGA prior to using it in daily practice [16]. A study in Dutch dietitians has demonstrated that already a full day training is very effective in improving both comprehensibility and difficulty of the PG-SGA [22].…”
Section: Discussionsupporting
confidence: 82%
“…Education most appropriately needs to target the physical examination from a nutrition or body composition perspective (Worksheet 4) and metabolic demands associated with fever and catabolic steroids (Worksheet 3). Previous research has found that the comprehension of the individual items of physical examination increased from 0.41 to 0.50 pretraining to 0.91e0.97 post-training after a single session of training [33]. Additionally, the level of difficulty improved from 0.13 to 0.17 pre-training to 0.53e0.71 post-training (p < 0.001), indicating that comprehension and ease of use significantly improved after receiving the one single session of training with the PG-SGA [33].…”
Section: Discussionmentioning
confidence: 95%
“…Especially HCPs who are not experienced in assessing a subjective evaluation of body composition in the context of nutritional status found this section to be the most difficult. However, both comprehensibility and difficulty improve with training [33]. The major limitation of the study is that study population was limited to cancer patients only, which can impact the generalizability of use beyond cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the PG-SGA assessment was carried out by either registered clinical dietitians or trained master students in clinical nutrition in accordance with the guidelines [30]. All personnel underwent training in the PG-SGA procedure, as training has been shown to increase comprehensibility [31]. Permission for use was obtained by the copyright holder of the instrument.…”
Section: The Pg-sgamentioning
confidence: 99%